PENGARUH PENERAPAN STRATEGI PEMBELAJARAN AKTIF TIPE COLLEGE BALL TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII MTsN PEKAN SELASA TAHUN PELAJARAN 2013/2014 - Gusmanengsih, Gusmanengsih; Rismen, Sefna; Mardiyah, Ainil (STKIP PGRI Sumbar, 2013)
This research is motivated by the students understanding of mathematical concepts are still low and less active students in learning activities. This study aims to determine the activity of student learning and understanding of mathematical concepts students ability to apply active learning strategy College Ball better type of student understanding of mathematical concepts that apply conventional learning in class VIII MTsN Pekan Selasa. This type of research is experimental research, the design of randomized trials on the subject. The population in this study were eighth grade students MTsN Pekan Selasa consists of three classes. Technique of random sampling, the sample is selected as the class as a class , Â as experimental and control classes. The instrument used in this study was the observation sheet and forms used test is the essay. Data analysis techniques are used to test the hypothesis is not a party with the help of MINITAB software. Based on the analysis of the data found that the two classes are normally distributed and homogeneous samples, then the hypothesis in this study received . Based on the observation that the analysis sheet from one meeting to meeting four activity increased student learning. It can be concluded that the students understanding of mathematical concepts that apply learning to use active learning strategies College Ball type better understanding of the mathematical concepts that students applying conventional learning in class VIII MTsN Pekan Selasa.